Mapping Tensions: Positioning Community Engagement Challenges as Generative Space - Jen Almjeld; Jennifer PeeksMease; Iona Black; Kerry Cresawn; Steven E. Grande; Juhong Christie Liu (The University of Alabama, 2022)
This research offers a contextual snapshot-via the applied tensional analysis (ATA) method-of common barriers that educators face when taking on community engagement work. A six-person research team interviewed 22 faculty and staff actively pursuing community partnerships at three different institutions of higher education in a single region. Participants' responses were coded to identify common barriers to engagement and the strategies that participants used to overcome those barriers. We draw on ATA (Mease, 2019) as a methodological approach that acknowledges tensions as critical entry points for understanding both the experiences of individual actors and the malleable structures from which those tensions emerge. This article does not attempt to offer one-size-fits-all strategies for community engagement. Instead, it offers ATA as a means for contextualizing specific tensions and strategies within local community engagement settings and for reframing those tensions as generative spaces for community engagement work.